2010
DOI: 10.1097/ncc.0b013e3181af5675
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Patient Experiences of Cancer Services in Regional Australia

Abstract: Numerous previous studies have suggested that cancer care in rural and regional Australia is fragmented and that rural and regional patients have less access to services. However, knowledge concerning inequality of health and cancer care in regional and rural settings is still inconclusive. The social and economic disadvantages in regional locations are often linked to insufficient resources and infrastructures to support cancer care and treatment. The aim of this study was to explore cancer patients' experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 39 publications
2
30
0
Order By: Relevance
“…Access to cancer care for people from rural Australia is an ongoing challenge (Drury & Inma ; Burris & Andrykowski ; White et al . , ; Smith et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Access to cancer care for people from rural Australia is an ongoing challenge (Drury & Inma ; Burris & Andrykowski ; White et al . , ; Smith et al .…”
Section: Introductionmentioning
confidence: 99%
“…; National Rural Health Alliance ; Smith ). Poor service accessibility in under‐funded, under‐resourced, rural communities is well documented in both Australia and internationally (Drury & Inma ; Burris & Andrykowski ; White et al . , ).…”
Section: Introductionmentioning
confidence: 99%
“…2008; Onega et al . 2008; Drury & Inma 2010), income (van Doorslaer et al . 2006), ethnicity (Shi & Stevens 2005) and health insurance (Hoffman & Paradise 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, participants indicated that there was a need to have contact with other people going through a similar situation and social outlets, as they were "lonely and bored" (McGrath, 2001). However, there is emerging evidence to suggest that the employment of Cancer Care Coordinators in rural and regional areas has reduced some of the challenges experienced by patients returning home from a specialist metropolitan hospital, giving subsequent rise to perceived wellbeing (Bray et al, 2011;Drury and Inma, 2010).…”
Section: Introductionmentioning
confidence: 96%